Features of the position of the ukrainian student societies of Eastern Halichina in the interwar period (1918–1939) through the prism of the analysis of the speeches of Milena Rudnytska - Гуменна, Ірина (Київський національний університет імені Тараса Шевченка, 2023)
Background. The interwar period (1918-1939) in Eastern Galicia was characterized by the politics of the Second Polish-Lithuanian Commonwealth, the influence of the international situation, and the struggle of the Ukrainian population for self-determination. During this period, Ukrainian student associations carried out active activities: from educational and cultural to nationally oriented work. Today, young people are also active participants in the processes of state formation, therefore, studying the national and cultural activities of Ukrainian student associations of Eastern Galicia, and, in particular, analyzing the conditions in which student associations operated, it is possible to single out the catalyzing and restraining factors encountered by the members of the associations in the conditions of the struggle for their rights and the creation of the Ukrainian state, to analyze how it affected the effectiveness of their efforts. Methods. When carrying out a comprehensive review of Diet speeches and taking into account the features of the interwar period and the politics of the Republic of Poland, it is necessary to adhere to the principle of objectivity, especially when analyzing emotional speeches that touched on the political situation of the period under study, and to use a number of methods, in particular, general scientific, interdisciplinary and actually historical. Results. The paper analyzes the Diet speeches of M. Rudnytska, a social and political figure, a member of the feminist movement, who was a member of the commission for foreign and educational affairs of the Polish Diet. The speeches highlighted events, the analysis of which makes it possible to assess the conditions of activity of Ukrainian student associations in Eastern Galicia and their impact on the attitude of student organizations. In the analyzed speeches, the active struggle for educational and cultural opportunities, the creation of the Ukrainian University, and the economic independence of student associations is noted. The article highlights the factors that most influenced the situation of the Ukrainian student movement and its activities. The support of the Ukrainian student associations of Eastern Galicia by public and political figures who represented the Western Ukrainian territories in the Diet, in particular, M. Rudnytska, is shown. Conclusion. On the basis of the analysis of the Diet speeches of deputy M. Rudnytska, the characteristic features of the position of Ukrainian student societies of Eastern Galicia, the peculiarities of their activities in the interwar period (1918–1939) in the national and cultural life of the Ukrainian people are highlighted. Keywords: Ukrainian Students Societies, Eastern Galicia, Milena Rudnytska, budget commission, national and cultural activities, pacification, Ukrainian University. DOI: https://doi.org/10.17721/1728-2640.2023.157.2

Вступ. Міжвоєнний період (1918-1939 рр.) у Східній Галичині характеризувався як власне політикою Другої Речі Посполитої, впливом міжнародної ситуації так і боротьбою українського населення за самовизначення. Українські студентські товариства здійснювали у цей період активну діяльність: від освітньо-культурницької до національно орієнтованої роботи. Сьогодні молодь є теж активним учасником процесів державотворення, тому вивчаючи національно-культурницьку діяльність українських студентських товариств Східної Галичини, а, зокрема, аналізуючи умови у яких діяли студентські товариства можна виокремити як каталізуючі, так і стримуючі фактори із якими зустрічались учасники товариств в умовах боротьби за свої права та створення української держави, проаналізувати як це впливало на результативність їх починань. Методи. Здійснюючи комплексний огляд сеймових промов та враховуючи риси міжвоєнного періоду й  політики Польської Республіки необхідно дотримуватись принципу об’єктивності, особливо при аналізі емоційних промов, які торкались політичної ситуації досліджуваного періоду та використовувати цілу низку методів, зокрема, загальнонаукових, міждисциплінарних та власне історичних. Результати. У праці проаналізовано сеймові промови громадсько-політичної діячки, учасниці феміністичного руху М. Рудницької, яка входила до комісії закордонних та освітніх справ Польського Сейму. У промовах висвітлено події, аналіз яких дає можливість оцінити умови діяльності українських студентських товариств Східної Галичини та їх вплив на ставище студентських організацій. У аналізованих промовах відзначається активна боротьба за освітньо-культурницькі можливості, створення Українського Університету, економічну самостійність студентських товариств. Важливим напрямком роботи українських студентських товариств була національно орієнтована діяльність, яка зустрічала дієвий супротив владних органів та органів охорони правопорядку. У статті виділено фактори, які найбільше впливали на становище українського студентського руху та його діяльність. Показано підтримку українських студентських товариств Східної Галичини громадсько-політичними діячами, які представляли західноукраїнські території у Сеймі, зокрема, М. Рудницькою. Висновки. На основі аналізу сеймових промов депутатки М. Рудницької виділено характерні риси становища українських студентських товариств Східної Галичини, особливості їх діяльності у міжвоєнний період (1918–1939 рр.)  у національно-культурному житті українського народу. Ключові слова: українські студентські товариства, Східна Галичина, Мілена Рудницька, бюджетна комісія, національно-культурна діяльність, пацифікація, Український Університет. DOI: https://doi.org/10.17721/1728-2640.2023.157.2
Особливості становища українських студентських товариств Східної Галичини міжвоєнного періоду (1918–1939 роки) крізь призму аналізу сеймових промов Мілени Рудницької
Keywords: Ukrainian Students Societies; Eastern Galicia; Milena Rudnytska; budget commission; national and cultural activities; pacification; Ukrainian University; history of Ukraine; українські студентські товариства; Східна Галичина; Мілена Рудницька; бюджетна комісія; національно-культурна діяльність; пацифікація; Український Університет; історія України